Agonism and the Possibilities of Ethics for HRM - Rhodes, Carl 1967-; Harvey, Geraint (2012)
This paper provides a critique and re-evaluation of the way that ethics is understood and promoted within mainstream Human Resource Management (HRM) discourse. We argue that the ethics located within this discourse focuses on bolstering the relevance of HRM as a key contributor to organizational strategy, enhancing an organization’s sense of moral legitimacy and augmenting organizational control over employee behaviour and subjectivity. We question this discourse in that it subordinates the ethics of the employment relationship to managerial prerogative. In response, we suggest a different model of the relationship between ethics and HRM—one that finds the possibility of ethics in the contestation and destabilization of HRM. Such ethics arises through resistance to moral normalization and the constraint of freedom and difference. The contribution of our paper is in theorising the possibilities of a relationship between ethics and HRM that does not place HRM at its centre, as chief intermediary of the ethics of the employment relationship, but rather sees HRM as being a powerful player in a set of what Mouffe calls ‘agonistic’ socio-ethical relations.
Keywords: Resistance; Politics; Organizational Ethics; Employee Relations; Human Resource Management; Agonism